2018
DOI: 10.1186/s12903-018-0612-5
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge and use of population-based methods for caries detection

Abstract: BackgroundSince the 1980s, a wide variety of methods have been proposed to measure dental caries in the population, demonstrating a lack of consensus regarding the procedure that should be used for this purpose. The current study investigated the methods that are known and used by public oral health researchers and professors as well as the reasons that lead to the choice of a particular method.MethodIn the context of an interview, a questionnaire was administered to public oral health researchers and professo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The most common dental caries indices used were WHO criteria 1987, 1997 and 2013 and the DMFT index proposed by Klein, Palmer and Knutson (1937). Castro et al (8) conducted an interview to investigate the populationbased caries detection methods and reported that DMFT index was the most known and used index. However, 95.7% were dissatisfied with the index yet continued to use it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common dental caries indices used were WHO criteria 1987, 1997 and 2013 and the DMFT index proposed by Klein, Palmer and Knutson (1937). Castro et al (8) conducted an interview to investigate the populationbased caries detection methods and reported that DMFT index was the most known and used index. However, 95.7% were dissatisfied with the index yet continued to use it.…”
Section: Discussionmentioning
confidence: 99%
“…Along with prevalence, it is also essential to evaluate the various indices used in the published literature for assessing caries, as different indices give varying results within the same populations (7). For example, the International Caries Detection and Assessment System (ICDAS) considers even white spots as caries, while the traditional Decayed Missing and Filled (DMF) index ignores noncavitated enamel lesions, leading to underestimation of caries (8).…”
Section: Introductionmentioning
confidence: 99%
“…Construct and discriminant validity was tested through associations and comparisons between the scores of the Indonesian version of the SEOH questionnaire and the global ratings using the Spearman's correlation coefficient and Kruskal‐Wallis test, respectively. Association between SEOH score and caries experience were tested to analyse external validity of caries existence as the health outcome …”
Section: Methodsmentioning
confidence: 99%
“…Association between SEOH score and caries experience were tested to analyse external validity of caries existence as the health outcome. 30,31…”
mentioning
confidence: 99%
“…DMFT index is the most used index for measurement of dental caries at population level. According to Castro et al [49] most of the study participant was of the opinion to use some other index yet continued to use it as according to them, they could not found more reliable method of measurement of dental caries. Almost all indices have limitation.…”
Section: Discussionmentioning
confidence: 99%